Effect of Internal Control System and Procedure Inventory Management Accounting - Arni Nuril Bisaroh; Lisna Lisnawati; Ahmad Andy Adinegara (LPPM Universitas Sebelas April, 2022)
Along with the development of the times, the progress of science and technology is experiencing increasingly rapid changes which make the awareness of health knowledge higher. This makes the Puskesmas, which is a health organization, strive to provide the best and quality services. One of the factors that play a role in the quality of Puskesmas services is the management of drug supplies carried out by the Puskesmas. It is very important to manage the supply of drugs and medical materials to prevent stock outs and overstocks in purchasing drugs and medical materials. Regulation of the Minister of Health of the Republic of Indonesia Number 74 of 2016 regulates pharmaceutical service standards at Puskesmas including the management of pharmaceutical preparations. The management is one of the pharmaceutical service activities, which starts from planning, requesting, receiving, storing, distributing, destroying and withdrawing, controlling, administration (recording and reporting) as well as monitoring and evaluation.